Pengaruh Literasi Digital Terhadap Hasil Belajar IPS di SMP Negeri 1 Selong Lombok Timur - Roziin Roziin; Padlurrahman Padlurrahman; Badarudin Badarudin (Universitas Hamzanwadi, 2024)
This research aims to determine the influence of digital literacy on the Integrated Social Sciences learning outcomes of students at SMP Negeri 1 Selong, East Lombok. The research method adopts a quantitative approach. The sampling technique was stratified random sampling. Stratified random sampling is a sampling technique in which the population is not homogeneous. To accurately describe the characteristics of a heterogeneous population, the population is divided into uniform strata, and each stratum is randomly sampled. The results of this study show that the R-squared value is 0.427. It can be concluded that the influence of digital skills on students' learning outcomes is 42.7%, and the rest is due to other influences. The R value of 0.31 is within the range of 0.21 to 0.40, so the relationship between these two variables belongs to the weak category. In the Coefficient column, you can see that the intercept value is 55.547 and the X value is 0.210. Therefore, we can create the regression equation: Y = 55.547 + 0.210X. Based on the regression equation, we can say that each unit increase in digital skills increases learning outcomes by 0.210.